The impact of high maternal body mass index on obstetric and perinatal outcomes - Sharma, Natasha; Patnaik, Manasi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The incidence of obesity has increased to pandemic proportions over the last 20 years. Maternal obesity is associated with a wide array of adverse maternal pregnancy outcomes and increased risks in the offspring. The aim of the study was to find the effect of obesity on maternal and perinatal outcome in obese women in comparison to those of normal weight women. Methods: The study was designed as a case-control study. Antenatal women with first trimester body mass index (BMI) of more than 30 kg/m2 constituted the cases and those with BMI between 18 and 24.9 kg/m2 formed the controls. Results: There was increased incidence of antepartum complications in obese women. Obese women had a significant history of prior treatment for infertility (p<0.00001). The incidence of gestational diabetes (OR 4.76, 95%CI 1.267-17.72 p=0.014), gestational hypertension (OR 3.05, 95%CI 1.01-9.20 p=0.04), induction of labor (OR 2.5, 95%CI 1.0-6.28 p=0.04), preeclampsia (OR 2.38, 95%CI 1.0-5.64 p=0.04, Caesarean section (OR 1.98, 95%CI 1.24-3.14 p=0.003), postpartum haemorrhage (OR 8.57, 95%CI 1.07-76.15 p=0.04) and wound infection (OR 8.57, 95%CI 1.07-76.15 p=0.04) and adverse neonatal outcomes such as higher mean birth weight (p<0.0001) and requirement of NICU (OR 2.79, 95%CI 1.33 -5.84 p=0.006) was higher in obese women. Conclusions: Obesity is an independent risk factor for adverse pregnancy outcomes and hence, interventions directed towards weight loss and prevention of excessive weight gain must begin in the preconception period.